Spiritual Well-Being in Women with Breast Cancer Receiving Palliative Care - Khalili, Seyedeh Maryam; Janati Ataei, Padideh; Hazini, Abdolrahim; Nasiri, Malihe; Torkzahrani, Shahnaz; Khoramabadi, Monir Sadat (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Breast cancer is the most common cancer in women with significant undesirable complications. Due to its life-threatening nature, the diagnosis of this disease increases spiritual needs and the need for palliative care. Palliative care has emerged as care that addresses explicitly gaps inherent in disease-centered approaches to enhance care quality in serious illness, both for patients and families and health care systems. Methods: This descriptive-comparative study was conducted on 200 women with breast cancer selected by convenience sampling from those visiting chosen hospitals of Tehran in 2018. Data were collected using a demographic-histopathologic form and Paloutzian-Ellison’s Spiritual Well-Being Scale, which was filled out in palliative care (n = 100) and routine care (n = 100) groups four weeks after the completion of therapy through interviews. The data obtained were analyzed in SPSS-21 using descriptive and inferential statistics. Results: Compared to those receiving routine care, the women with breast cancer who were receiving palliative care had higher scores in religious well-being (P < 0.509) and total spiritual well-being (P < 0.167), although not in a statistically significant way. Meanwhile, the palliative care group obtained significantly higher scores in existential well-being compared to the routine care group (P < 0.007). Conclusions: Developing programs to improve spiritual well-being in patients with breast cancer by incorporating palliative care into medical interventions can be beneficial.